Information
You have already completed the quiz before. Hence you can not start it again.
You must sign in or sign up to start the quiz.
You have to finish following quiz, to start this quiz:
Loading...
-
Question 1 of 4
Write “F” if the binomial is a Factor and “N” if it is not a Factor of the polynomial:
P(x)=x3+2x2-5x-6P(x)=x3+2x2−5x−6
Incorrect
Loaded: 0%
Progress: 0%
0:00
Note that if r=0r=0, then (x-a)(x−a) is a Factor of P(x)P(x)
(a)(a) Identify if (x-2)(x−2) is a factor of P(x)=x3+2x2-5x-6P(x)=x3+2x2−5x−6.
First, label the variable aa by equating the binomial to 00 and solving for xx
x-2x−2 |
== |
00 |
x-2x−2 +2+2 |
== |
00 +2+2 |
Add 22 to both sides |
xx |
== |
22 |
Next, substitute aa into the polynomial to solve for rr
P(x)=x3+2x2-5x-6P(x)=x3+2x2−5x−6
a=2a=2
P(a)P(a) |
== |
rr |
Remainder Theorem |
P(a)P(a) |
== |
a3+2a2-5a-6a3+2a2−5a−6 |
Replace xx with aa |
P(2)P(2) |
== |
23+2(2)2-5(2)-623+2(2)2−5(2)−6 |
Substitute a=2a=2 |
|
== |
8+2(4)-10-68+2(4)−10−6 |
|
== |
8+8-10-68+8−10−6 |
|
== |
16-1616−16 |
rr |
== |
00 |
Since r=0r=0, we can say that (x-2)(x−2) is a factor of P(x)=x3+2x2-5x-6P(x)=x3+2x2−5x−6
(b)(b) Identify if (2x-1)(2x−1) is a factor of P(x)=x3+2x2-5x-6P(x)=x3+2x2−5x−6.
First, label the variable a by equating the binomial to 0 and solving for x
2x-1 |
= |
0 |
2x-1 +1 |
= |
0 +1 |
Add 1 to both sides |
2x |
= |
1 |
2x÷2 |
= |
1÷2 |
Divide both sides by 2 |
|
x |
= |
12 |
Next, substitute a into the polynomial to solve for r
P(a) |
= |
r |
Remainder Theorem |
P(a) |
= |
a3+2a2-5a-6 |
Replace x with a |
|
P(12) |
= |
(12)3+2(12)2-5(12)-6 |
Substitute a=12 |
|
|
= |
18+2(14)-52-6 |
|
|
= |
18+48-208-488 |
|
r |
= |
-638 |
Since r≠0, we can say that (2x−1) is not a factor of P(x)=x3+2x2−5x−6
(c) Identify if (x+3) is a factor of P(x)=x3+2x2-5x-6.
First, label the variable a by equating the binomial to 0 and solving for x
x+3 |
= |
0 |
x+3 -3 |
= |
0 -3 |
Subtract 3 from both sides |
x |
= |
-3 |
Next, substitute a into the polynomial to solve for r
P(a) |
= |
r |
Remainder Theorem |
P(a) |
= |
a3+2a2-5a-6 |
Replace x with a |
|
P(-3) |
= |
(-3)3+2(-3)2-5(-3)-6 |
Substitute a=-3 |
|
|
= |
-27+2(9)+15-6 |
|
= |
-27+18+15-6 |
|
= |
-33+33 |
r |
= |
0 |
Since r=0, we can say that (x+3) is a factor of P(x)=x3+2x2-5x-6
(a) Factor
(b) Not a factor
(c) Factor
-
Question 2 of 4
Solve for the remainder of:
(8x+x2+3)÷(3+x)
Incorrect
Loaded: 0%
Progress: 0%
0:00
Long Division
Use long division when a polynomial is divided by a binomial
Note that if r=0, then (x-a) is a Factor of P(x)
Method One
Find the remainder using long division
First, arrange the terms in descending order of powers.
P(Polynomial) |
= |
8x+x2+3 |
|
= |
x2+8x+3 |
Divisor |
= |
3+x |
|
= |
x+3 |
< |
= |
 |
Next, solve for each term of the quotient
First term of the quotient:
Divide the first term of the Polynomial by the first term of the Divisor. Place this above the Polynomial
x2÷x |
= |
x |
 |
Multiply x to the divisor. Place this under the Polynomial
x(x+3) |
= |
x2+3x |
 |
Subtract x2+3x and write the difference one line below
Drop down 3 and repeat the process to get the second term of the quotient
Second term of the quotient:
Divide the first term of the bottom expression by the first term of the Divisor. Place this above the Polynomial
5x÷x |
= |
5 |
 |
Multiply 5 to the divisor. Place this under the Polynomial
5(x+3) |
= |
5x+15 |
 |
Subtract 5x+15 and write the difference one line below
-12 is not divisible by the divisor (x+3) anymore, hence r=-12
Method Two
Find the remainder using remainder theorem
First, label the variable a by equating the divisor to 0 and solving for x
x+3 |
= |
0 |
x+3 -3 |
= |
0 -3 |
Subtract 3 from both sides |
x |
= |
-3 |
Next, substitute a into the polynomial to solve for r
P(a) |
= |
r |
Remainder Theorem |
P(a) |
= |
8a+a2+3 |
Replace x with a |
P(-3) |
= |
8(-3)+(-3)2+3 |
Substitute a=-3 |
|
= |
-24+9+3 |
r |
= |
-12 |
-
Question 3 of 4
Solve for the remainder of:
x4-3x3+2x+8x-2
Incorrect
Loaded: 0%
Progress: 0%
0:00
Long Division
Use long division when a polynomial is divided by a binomial
Note that if r=0, then (x-a) is a Factor of P(x)
Method One
Find the remainder using long division
First, notice that the term with the power of 2 is missing. Add this term to the polynomial before using long division
P(Polynomial) |
= |
x4-3x3+2x+8 |
|
= |
x4-3x3+0x2+2x+8 |
Divisor |
= |
x-2 |
 |
= |
 |
Next, solve for each term of the quotient
First term of the quotient:
Divide the first term of the Polynomial by the first term of the Divisor. Place this above the Polynomial
x4÷x |
= |
x3 |
 |
Multiply x3 to the divisor. Place this under the Polynomial
x3(x-2) |
= |
x4-2x3 |
 |
Subtract x4-2x3 and write the difference one line below
Drop down 0x2 and repeat the process to get the second term of the quotient
Second term of the quotient:
Divide the first term of the bottom expression by the first term of the Divisor. Place this above the Polynomial
-x3÷x |
= |
-x2 |
 |
Multiply -x2 to the divisor. Place this one line below
-x2(x-2) |
= |
-x3+2x2 |
 |
Subtract -x3+2x2 and write the difference one line below
Drop down 2x and repeat the process to get the third term of the quotient
Third term of the quotient:
Divide the first term of the bottom expression by the first term of the Divisor. Place this above the Polynomial
-2x2÷x |
= |
-2x |
 |
Multiply -2x to the divisor. Place this under the Polynomial
-2x(x-2) |
= |
-2x2+4x |
 |
Subtract -2x2+4x and write the difference one line below
Drop down 8 and repeat the process to get the fourth term of the quotient
Fourth term of the quotient:
Divide the first term of the bottom expression by the first term of the Divisor. Place this above the Polynomial
-2x÷x |
= |
-2 |
 |
Multiply -2 to the divisor. Place this under the Polynomial
-2(x-2) |
= |
-2x+4 |
 |
Subtract -2x+4 and write the difference one line below
4 is not divisible by the divisor (x-2) anymore, hence r=4
Method Two
Find the remainder using remainder theorem
First, label the variable a by equating the divisor to 0 and solving for x
x-2 |
= |
0 |
x-2 +2 |
= |
0 +2 |
Add 2 to both sides |
x |
= |
2 |
Next, substitute a into the polynomial to solve for r
P(a) |
= |
r |
Remainder Theorem |
P(a) |
= |
a4-3a3+2a+8 |
Replace x with a |
P(2) |
= |
24-3(2)3+2(2)+8 |
Substitute a=2 |
|
= |
16-3(8)+4+8 |
|
= |
16-24+4+8 |
r |
= |
4 |
-
Question 4 of 4
Solve for the remainder of:
(a) x4-5x3+3x2+8x-2
(b) 3x4-x2+2x+6x+1
Incorrect
Loaded: 0%
Progress: 0%
0:00
(a) Solve for the remainder of x4-5x3+3x2+8x-2.
First, label the variable a by equating the divisor to 0 and solving for x
x-2 |
= |
0 |
x-2 +2 |
= |
0 +2 |
Add 2 to both sides |
x |
= |
2 |
Next, substitute a into the polynomial to solve for r
P(a) |
= |
r |
Remainder Theorem |
P(a) |
= |
a4-5a3+3a2+8 |
Replace x with a |
P(2) |
= |
(2)4-5(2)3+3(2)2+8 |
Substitute a=2 |
|
= |
16-5(8)+3(4)+8 |
|
= |
16-40+12+8 |
r |
= |
-4 |
(b) Solve for the remainder of 3x4-x2+2x+6x+1.
First, label the variable a by equating the divisor to 0 and solving for x
x+1 |
= |
0 |
x+1 -1 |
= |
0 -1 |
Subtract 1 from both sides |
x |
= |
-1 |
Next, substitute a into the polynomial to solve for r
P(a) |
= |
r |
Remainder Theorem |
P(a) |
= |
3a4-a2+2a+6 |
Replace x with a |
P(-1) |
= |
3(-1)4-(-1)2+2(-1)+6 |
Substitute a=-1 |
|
= |
3(1)-1-2+6 |
|
= |
3-1-2+6 |
r |
= |
6 |